In the presence of witnesses: petitioning and judicial 'publics' in western India, c. 1600-1820 - O'Hanlon, R (Cambridge University Press, 2019)
Indian observers of the East India Company’s emerging political order in the late eighteenth century were, as is well known, struck by the inaccessibility of its officials to their Indian subjects. Both Indo-Muslim traditions of akhlāq, and Sanskrit-influenced norms for nīti or political ethics, emphasised the duties of rulers, or those they deputised, to be vigilant in their watch over the condition of their subjects, to listen to their concerns, and offer them regular opportunities to present their pleas for justice. As the Company’s Bengal government struggled to develop effective judicial systems, its own servants became sharply aware of the difficulty of balancing accessibility with the disorder that might overwhelm its courts unless petitioners could be channelled into a formal judicial system. By the 1820s in western India, and certainly in the mind of the first Governor of Bombay Mountstuart Elphinstone, Bengal’s judicial system had become a byword for paralysis, with its delays, ill-informed or inert judges and the endless layers of intermediates interposed between petitioners and magistrates. He contrasted it with the situation in western India. ‘Here, every man above the rank of a Hircarrah sits down before us, and did before the Paishwa; even a common Ryot, if he had to stay any time, would sit down on the ground’. With their deep local knowledge and familiar principles of procedure, traditional ‘panchayat’ assemblies in particular ‘retained in a great degree the confidence of the people’. He urged that the panchayat be retained as a local part of the Bombay government’s own judicial system.